Coastal upwelling in Norway recorded in Great Scallop shells. (30th April 2015) - Jolivet, Aurélie; Asplin, Lars; Strand, Øivind; Thébault, Julien; Chauvaud, Laurent
Abstract The shells of bivalve mollusks have been shown to contain a wealth of information about the environment in which the organisms lived as well as about their life histories. Shells of the Great Scallop Pecten maximus were collected in 1987 and 1988 at 15–25 m depth close to the Austevoll islands (Norway). A sharp slowdown in growth was detected in 1986 for all age classes, resulting in a growth‐rate decrease of nearly 45% over 10 d. Measurements of stable isotopes (δ18O and δ13C) in four specimens suggested that this slowdown was concurrent with a drop in water temperature. In situ measurements of environmental parameters (temperature, salinity, wind) and data from a numerical coastal model system (NorKyst‐800) confirmed that a temperature drop of 3°C occurred in July 1986 due to a sudden change in wind direction and speed along the western coast of Norway. These northerly winds parallel to the coast induced an upwelling of deep cold water along the coast. Thus, the present study demonstrated a clear relationship between regional climatic phenomena acting on an oceanographic process and the growth of a benthic invertebrate. Bivalve shells should be used to describe and characterize local upwelling events, for example, in terms of duration and intensity, in current environments and in paleoenvironments.